Prediction of fatigue level during exercise in virtual reality environment for hajj pilgrimage - Dayang Hjh Tiawa, Awang Hj Hamid; Abdul Hafidz, Omar; Adam, Jait; Norashikin, Yusof; Zulkifli, Ahmad@Manap (2019)
Strenuous activities, especially through the eight days of the Hajj pilgrimage journey, may cause exhaustion for the Hajj pilgrims after completing each stage. Environmental factors such as being in overcrowded places and having to endure hot temperatures alongside continuous vigorous activities during the Hajj can result in serious exhaustion where individual body muscles and the cardio-respiratory systems are affected, resulting in muscle cramps, dehydration and possibly illness such as fever, hypertension, stroke, asthma and heart attack. This paper aims to introduce a wearable device that can assist the pilgrims to monitor their exhaustion threshold. To test this, 30 healthy people who are about to perform hajj were chosen as respondents for the study. These subjects performed fatigue- induced exercises by walking or running on a treadmill which is integrated with a 3D virtual reality environment of Makkah. The speed of the treadmill increased its intensity at every 2 minute interval from 4 km per hour to 12km per hour until the subjects’ exhaustion threshold is reached. Simultaneously, heart rate, blood pressure and muscle fatigue were closely monitored using the developed device attached to their wrists. This device uses an electrocardiogram (ECG) and an electromyography (EMG) measurement and produces three different colour signals ranging from green, yellow and red to indicate the subjects’ exhaustion level. The data collection of each subject was then analysed using the SPSS software and also modelled in MATLAB software for the ANN method. As a result, the accuracy of prediction model presented from this study is 89.3%, indicating a high indicator for the fatigue level. Overall, this study is expected to be beneficial for hajj pilgrims who wish to evaluate their own body fitness when preparing for their Hajj pilgrimage.